(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Intensive use of social media threat to physical health, visual disorders is one them. A cross-sectional analytical study was conducted to identify the visual hazards of social media users among students of public and private universities in Dhaka city. Materials and methods: A pretested, semi-structured standard questionnaire and randomized sampling technique was used to collect the data, the number of calculated sample size was 726. Results: Study revealed that mean age of the respondents of public university were 21.551.93 years and private university were 21.141.62 years. It was found that 28.10%, 9.90%, 17.90%, 10.70%, 6.60%, 22.60%, 8.50%, 0.60%, 18.70%, 2.80%, 1.90%, 2.80% and 0.60% of the respondents of public university complained headache, dry eye syndrome, eye strain, burning, itching, tearing eyes, irritated eyes, squinting, blurry vision, double vision, temporary change in color vision, trouble seeing at night, distorted vision respectively and that of the students of private university were 36.60%, 9.60%, 22.00%, 12.70%, 11.80%, 31.70%, 14.90%, 5.50%, 15.70%, 6.90%, 6.30%, 6.10% and 0.80% respectively. Social media disorders influence significantly on eyestrain of the students of both public and private universities. Conclusion: Social media had different types of visual hazards among the students of both public and private universities in Dhaka city. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 3-7